Proteome analysis reveals antiangiogenic environments in chronic wounds of diabetes mellitus type 2 patients. Issue 17 (30th July 2013) - Krisp, Christoph; Jacobsen, Frank; McKay, Matthew J.; Molloy, Mark P.; Steinstraesser, Lars; Wolters, Dirk A.
<x xml:space="preserve">Abstract</x> In contrast to normal healing wounds, chronic wounds commonly show disturbances in proteins regulating wound healing processes, particularly those involved in cell proliferation and protein degradation. Multidimensional protein identification technology MS/MS was conducted to investigate and compare the protein composition of chronic diabetic foot exudates to exudates from split‐skin donor sites of burn victims otherwise healthy. Spectral counting revealed 188 proteins differentially expressed (more than twofold and p‐value <0.05) in chronic wounds. Most were involved in biological processes including inflammation, angiogenesis, and cell mortality. Increased expression of the inflammatory response stimulating S100 proteins, predominantly S100A8 and S100A9 (almost tenfold), was identified. Matrix metalloproteinases (MMPs) MMP1, MMP2, and MMP8 were identified to be elevated in chronic wounds with significant impact on collagen degradation and tissue destruction. Further, proteins with antiangiogenic properties were found at higher expression levels in chronic wounds. Reduced angiogenesis leads to drastic shortage in nutrition supply and causes increased cell death, demonstrated by Annexin A5 exclusively found in chronic wound exudates. However, excessive nucleic and cytosolic material infers cell death occurring not only by apoptosis but also by necrosis. In conclusion, mass spectrometric investigation of exudates from chronic wounds demonstrated dramatic impairment in wound repair with excessive inflammation, antiangiogenic environment, and accelerated cell death.